Association of ABCB1 gene variants, plasma antidepressant concentration, and treatment response: Results from a randomized clinical study. (February 2016) - Breitenstein, Barbara; Scheuer, Sandra; Brückl, Tanja Maria; Meyer, Jobst; Ising, Marcus; Uhr, Manfred; Holsboer, Florian
Abstract: P-glycoprotein, encoded by the ABCB1 gene, functions as an ATP-driven efflux pump in the blood–brain barrier, extruding its substrates and thereby limiting their passage into the brain. ABCB1 polymorphisms predicted antidepressant drug response: Minor allele carriers of SNPs rs2032583 and rs2235015 had higher remission rates than major allele homozygotes. The aim of the current study was to evaluate an ABCB1 genotype-dependent efficacy of a quick dose escalation strategy. Depressed inpatients (n = 73) treated with antidepressants that are P-glycoprotein substrates were randomly assigned to a standard or high dose condition for 28 days. HAM-D scores, adverse effects and plasma antidepressant concentration were measured weekly and tested among two intronic SNPs rs2032583 and rs2235015. A treatment as usual control sample (n = 128) was retrospectively matched to the study group by gender, age, and diagnosis. There was a significant interaction of genotype x plasma antidepressant concentration: Minor allele carriers of rs2032583 [ F (1, 65) = 7.221, p = 0.009] and rs2235015 [ F (1, 65) = 4.939, p = 0.030] whose plasma drug concentration were within recommended range had a greater symptom reduction at study endpoint which exceeded the therapeutic benefit of the treatment as usual group [for rs2032583: F (1, 163) = 4.366, p = 0.038]. Minor allele carriers of rs2032583 with high plasma drug levels had more sleep-related side effects than major allele homozygotes with high plasma drug levels. The treatment of MDD can be optimized by ABCB1 genotyping combined with monitoring of plasma drug concentrations: For minor allele carriers of rs2032583 and rs2235015, plasma antidepressant levels should not exceed the recommended range in order to obtain optimal treatment outcome. Highlights: ABCB1 variants interact with plasma antidepressant levels to predict the antidepressant treatment efficacy. For minor allele carriers (rs2032583), plasma drug levels should not exceed recommended range to obtain best treatment outcome. Among carriers, the benefit of P-gp substrate treatment in recommended plasma drug range exceeds the benefit of TAU. Carriers with high plasma drug levels have more sleep-related side effects than major allele homozygotes with high plasma levels. The treatment of MDD can be optimized by ABCB1 genotyping combined with monitoring of plasma drug concentrations.